EFFORTS TO IMPROVE MATHEMATICS LEARNING OUTCOMES USING DIRECT LEARNING MODELS IN CLASS IV OF SD IP MA'ARIF NU 1 AL FIRDAUS - Nur Fadlilah, Dewi; Ariyanto, Bambang; Astuti, Dwilita (EDU AKOMMEDIA : JURNAL ILMU PENDIDIKAN, 2024)
This research uses a classroom action research model, to determine the increase in student mathematics learning outcomes using the direct learning model at SD Islam Plus Ma'arif NU Al-Firdaus Pasir Sakti East Lampung, the problem faced is the low learning outcomes of students, so by using the learning model This gives students the opportunity to specifically observe, remember and imitate what their teacher models or exemplifies. The results of the research show that learning in the pre-cycle increased by 58% to 62%, so the average increase was 4% in cycle 1, while the increase in learning outcomes in cycle II experienced an average increase of 92% with an average increase of 12%, so This research shows a very significant increase in learning outcomes.